Reinforcing or Fragmenting Trust? Public Service Reform and the Paradox of Accountability in Nepal (Prashasan: The Nepalese Journal of Public Administration, 2025)
This article examines the complex and often contradictory impact of public service reform on the theory and practice of public accountability, with a specific focus on the critical case of Nepal. While global managerial reforms-spanning New Public Management (NPM), Network Governance, and Digital Governance-have theoretically reshaped accountability from a hierarchical, process-oriented mechanism into a multifaceted, performance-based network, their practical outcomes are deeply ambiguous. Drawing on extensive document analysis, secondary data, and existing empirical studies, this study argues that in Nepal, reforms have successfully created a strong de jure design for accountability through federalism, independent oversight bodies, and digitalization. However, the de facto strengthening of accountability is severely constrained by a nexus of institutional practices, including systemic political patronage, a critical “audit-action gap,” significant sub-national capacity constraints, and pervasive elite capture. The article introduces the concept of the “accountability implementation gap” to describe this landscape. The findings suggest that in contexts where formal institutional change dramatically outpaces the evolution of political and administrative culture, technical and legal reforms alone are insufficient to build a deeply embedded culture of public accountability. The article concludes that for trust to be genuinely reinforced, a second generation of reforms focused on political integrity and administrative behavioral change is imperative.